ADD3 Deletion in Glioblastoma Predicts Disease Status and Survival - Kiang, Karrie Mei-Yee; Sun, Stella; Leung, Gilberto Ka-Kit (Frontiers in Oncology, 2021)
Loss of heterozygosity (LOH) on chromosome 10 frequently occurs in gliomas. Whereas genetic loci with allelic deletion often implicate tumor suppressor genes, a putative tumor suppressor Adducin3 (ADD3) mapped to chromosome 10q25.2 was found to be preferentially downregulated in high grade gliomas compared to low grade lesions. In this study, we unveil how the assessment of ADD3 deletion provides clinical significance in glioblastoma (GBM). By deletion mapping, we assessed the frequency of LOH in forty-three glioma specimens using five microsatellite markers spanning chromosome 10q23-10qter. Data were validated in a TCGA cohort with 203 GBM patients. We found that allelic loss in both D10S173 (ADD3/MXI1 locus) and D10S1137 (MGMT locus) were positively associated with tumor grading and proliferative index (MIB-1). However, LOH events at only the ADD3/MXI1 locus provided prognostic significance with a marked reduction in patient survival and appeared to have diagnostic potential in differentiating high grade gliomas from low grade ones. Furthermore, we showed progressive loss of ADD3 in six out of seven patient-paired gliomas with malignant progression, as well as in recurrent GBMs. These findings suggest the significance of ADD3/MXI1 locus as a promising marker that can be used to refine LOH10q assessment. Data further suggest the role ADD3 as a novel tumor suppressor, whereby the loss of ADD3 is indicative of a progressive disease that may at least partially account for rapid disease progression in GBM. This study revealed for the first time downregulation of ADD3 on the genetic level resulted from copy number deletion.